EFFECTS OF LEAF EXTRACT ON IN VITRO POLLEN GERMINATION AND POLLEN TUBE GROWTH IN LUFFA AEGYPTICA MILL. AND MOMORDICA CHARANTIA L. - P. P. PRAJAPATI; B. K. JAIN (The Bioscan, 2011)
Luffa aegyptica Mill. (spongy gourd) and Momordica charantia L.(bitter gourd) are the members of the family Cucurbitaceae. In Luffa aegyptica Mill., at 60 minute stage, among all concentrations of plant leaf extract, the maximum percentage of pollen germination and tube growth reported are 55.68% and 55.68% respectively in the modified basal medium having 2 drops/2mL concentration. These values are less than those obtained in control i.e. 85.00% and 81.25% respectively. While, in Momordica charantia L., at 60 minute stage, among all concentrations of plant leaf extract, the maximum percentage of pollen germination and tube growth observed are 49.38% and 28.39% respectively in the modified basal medium having 1 drops / 2mL concentration. These values are less than those noted in control i.e. 70.10% and 65.97% respectively. Increasing concentration of leaf extract in basal medium shows inhibitory effects.